BIM Sociotechnology: Situational Awareness as a Strategy for Enhancing Collaboration in BIM-Enabled Education within the GCC Context - راية محمود عطور; أحمد محمد أحمد (تجسير, 2023)
The education and industry of architecture and engineering disciplines are being transformed by Building Information Modelling (BIM) through digitization. Recent literature shows that BIM is in reality 90% sociology and 10% technology, despite the perception that it is 90% technology and 10% sociology. Without social interventions within technological models, barriers and limitations that are evident in the social culture of an institution could result in being reflected in dead-ended technical and technological structures and solutions. For this, concepts of social sustainability and cultural resilience are promoted by proposing socio-technical solutions relying on the theoretical model of Situational Awareness (SA) as a cornerstone in this research. The investigation method on the link between BIM-enabled Education and SA is done through multiple interviews within the academic sector of multiple educational institutions within the Gulf Cooperation Council (GCC). The results of this study could design a preliminary framework for approaching technical solutions to social dilemmas and thus help in enhanced implementation and collaboration in BIM-enabled education in the GCC.